Health care practice and life pattern of elderly women attending in a selected geriatric hospital in Dhaka city - Begum, Mahjabeen Sultana; Hossain, Mohammad Zaid; Deb, Sudip Ranjan; Khan, Md Mosaraf Hossain; Rahman, Mostafizur; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2013)
Objective: The study was carried out to find out the health care seeking practice among the elderly women attending a selected hospital in Dhaka city. Materials and methods: This was a cross sectional study and included 164 women aged 60 years and above. The study was carried out from March to June, 2001, at Prabin Hitayishi Hospital, Bangladesh Associated of Aged and Institute of Geriatric Medicine (BAAIGM), Agargaon, Sher E Bangla Nagar, Dhaka. Results: In the present study, 58.5% women were aged less than 65 years, 51.2% were illiterates, 65.9% were married, only 7.3% were living with their spouse, 86.6% were housewives, only 9.8% had self income, 25.6% were earning between Taka 10,001 and 15,000 per month, and 41.5% were staying in families with 7 8 members, 90.2% had regular daily bath, 80.5% with soap, 90.2% brushed their teeth at least once a day, only 12.2% were taking regular exercise, 70.7% had knowledge about self health care, however, only 22% were on regular health check up, 12.2% women thought egg, milk, fish, meat and fruits were good for health. Regarding old age diseases, 43.9% knew about diabetes, 39% high blood pressure, 36.6% heart, 17.1% respiratory and 2.4% orthopaedic diseases. Most common diseases were eye (26.8%), cardiovascular and orthopaedic (19.5%) and ENT (14.6%). Other diseases were gastrointestinal (9.8%), respiratory (7.1%), dental and endocrine (4.9%). Conclusion: Old women of our society should be made aware on old age diseases and self health care practices. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15602 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 30-33